Perencanaan dan Implementasi Protokol Video Conference pada Keluarga Narapidana Penghuni Lembaga Pemasyarakatan Menggunakan Smartphone - Desy Damasari Nazilah (Politeknik Negeri Malang, 2017)
The development of communication technology today has had a major impact and changes to the processdelivery of information. Video Conference is a method of conveying information which is quite attractive for distance communication far. In this study, the application of the video conference application is used as a prototype to support the facility in the Correctional Institution. The tools and materials used in the research include web servers, users(Android), Raspberry Pi, webcam, and monitor. The software application used in the research, namely,Dreamweaver is used for web design, webRTC for video conferencing protocol and Wireshark forcapture network traffic during videoconverence access, so that it can be known QOS parameters (delay, throughput, and packet loss) are generated. Based on the tests that were carried out during the video conference process, the results were obtainedcapture from several application protocols that support video conferencing, namely TCP, UDP, and STUN. . PackageThe best loss is the TCP protocol, which is 0%, the best delay is the UDP protocol with an average delay27.06 ms, the best throughput is obtained on the STUN protocol with an average throughput of 5.273 Mbit / s